PENGARUH KOMPETENSI DAN E-GOVERNMENT TERHADAP KUALITAS PELAYANAN PUBLIK PADA PENGADILAN AGAMA PALU - Ira Rahmawati (Katalogis, 2018)
The purpose of this research are: 1) To explore and analyze the influence of competency and e-government on the quality of public services at the office of religious court in Palu; 2) to explore and analyze the influence of competency on the quality of public services at the office of religious court in Palu; 3) To explore and analyze the influence e-government on the quality of public services at The Office Of Religious Court in Palu. Type of research is descriptive involving 52 civil servants, 7 honorary staff, and 1 voluntary staff The Office Of Religious Court in Palu who selected as samples by using census technique. Based on multiple linear regression analysis, the result finds that : 1) competency and e-government simultaneously have positive and significant influence on the quality of public services at the office of religious court in Palu; 2) partially, competency has positive and significant on the quality of public services at the office of religious court in Palu; 3) partially, E-government has positive and significant influence on the quality of public services at the office of religious court in Palu.